Saying it out loud: explicit equity prompts for public health organization resilience - Haworth-Brockman, Margaret; Betker, Claire; Keynan, Yoav (Frontiers in Public Health, 2023)
Introduction In the early days of the COVID-19 pandemic there were numerous stories of health equity work being put “on hold” as public health staff were deployed to the many urgent tasks of responding to the emergency. Losing track of health equity work is not new and relates in part to the need to transfer tacit knowledge to explicit articulation of an organization’s commitment to health equity, by encoding the commitment and making it visible and sustainable in policy documents, protocols and processes. Methods We adopted a Theory of Change framework to develop training for public health personnel to articulate where and how health equity is or can be embedded in their emergency preparedness processes and documents. Results Over four sessions, participants reviewed how well their understanding of disadvantaged populations were represented in emergency preparedness, response and mitigation protocols. Using equity prompts, participants developed a heat map depicting where more work was needed to explicitly involve community partners in a sustained manner. Participants were challenged at times by questions of scope and authority, but it became clear that the explicit health equity prompts facilitated conversations that moved beyond the idea of health equity to something that could be codified and later measured. Over four sessions, participants reviewed how well their understanding of disadvantaged populations were represented in emergency preparedness, response and mitigation protocols. Using equity prompts, participants developed a heat map depicting where more work was needed to explicitly involve community partners in a sustained manner. Participants were challenged at times by questions of scope and authority, but it became clear that the explicit health equity prompts facilitated conversations that moved beyond the idea of health equity to something that could be codified and later measured. Discussion Using the indicators and prompts enabled the leadership and staff to articulate what they do and do not know about their community partners, including how to sustain their involvement, and where there was need for action. Saying out loud where there is – and is not – sustained commitment to achieving health equity can help public health organizations move from theory to true preparedness and resilience.